Study on fracture mechanics of granite based on digital speckle correlation method. (1st June 2020) - Zhao, Tong-bin; Zhang, Wei; Gu, Shi-tan; Lv, Yan-wei; Li, Zhan-hai
Abstract: Crack propagation length (CPL) and stress intensity factor (SIF) are key parameters to solve rock failure issue when using fracture mechanics. In order to study the evolution law of the two factors during the mode Ⅰ fracture evolution, a series of three-point bending tests of granite specimens with central cracks were carried out. During the loading process, digital speckle correlation method (DSCM) was used to monitor the full field deformation. The crack opening displacement is first determined through the full field displacement data. Then, this value is compared with those calculated by ASTM and Tada equations. Additionally, a virtual extensometer is arranged at the crack tip. The crack tip position and CPL are determined by the measurement hybrid method. Results show that the crack length evolution can be divided into three stages: crack initiation, crack tip formation and crack propagation. At the 90% peak load, the crack propagation rate increases rapidly until the rock failure. During this period, the crack growth consists of 87% of the total length. While the increasing rate of SIF presents quick-slow-quick evolution law, and SIF reaches the maximum at the peak load. When the crack forms, CPL and SIF all experience rapid increase at the deformation point and reach the maximum during the instable failure of rock.